Effectiveness of Smart Class on Achievement of Students in Science at the Upper Primary Level - Devpura, Vibha (JOURNAL OF INDIAN EDUCATION, 2017)
The present study investigated the effectiveness of smart class on achievement of students in science at upper primary level. The sample consisted of 60 students of class VII of a public school of Udaipur city. The school was selected purposively and students were selected randomly. An experimental method was employed in the study. A true experimental design, i.e., pre-test, post-test equivalent group design was used. A pre-test was administered before the treatment, then a treatment of 21 days was given. The experimental group was taught through smart class, whereas control group was taught through conventional method of teaching. Then a post-test (achievement test) was administered on both the groups. A t-test was used for the analysis of data. The experimental group was found having significantly higher achievement scores as compared to the control group.